Advertisement Representation in North Sulawesi : Representasi Iklan di Sulawesi Utara - Vany Kamu; Nova Olvie Mandolang; Christo Rilco Pua; Garryn Christian Ranuntu (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Advertising is a form of communication media that has a persuasive nature, where the aim is to convince viewers to trust and use the product or service being promoted. The form of advertising can be in the form of images, photos, and words, even a combination of both, or leaflets, banners, digital advertisements, or individuals. Research on advertising is an important step to introduce the context, significance, and purpose of the research. Advertising, as an integral element in the world of marketing and communication, has a very vital role in influencing consumer perceptions, attitudes, and behavior. In the digital era and globalization, advertising is not only a means of promoting products or services, but also reflects trends, cultural values, ​​and social dynamics. This research will use a descriptive research approach to answer research questions. The choice of descriptive research with a quantitative approach is considered appropriate to the objectives of this research. Apart from playing a role in forming meaning, representation also plays a role in forming identity. Identity is a product of production that is constantly in the process of change, indicating that identity is "always formed within, not outside, representation." The analysis applied in this research is based on Hall's theory of representation. Representation combines existing signs to form meaning, and because everyone has different empirical experiences, the nature of representation becomes unstable and is never limited to just one interpretation.